The Role of RaxST, a Prokaryotic Sulfotransferase, and RaxABC, a Putative Type I Secretion System, in Activation of the Rice XA21-Mediated Immune Response - Pamela C. Ronald (Scientifica)
Tyrosine sulfation is an important posttranslational modification that determines the outcome of serious diseases in plants and animals. We have recently demonstrated that the plant pathogen Xanthomonas oryzae pv. oryzae (Xoo) carries a functional sulfotransferase (RaxST). raxST is required for activation of rice Xa21-mediated immunity indicating the critical, but unknown, function of raxST in mediating the Xoo/rice interaction. The raxST gene resides in the same operon (raxSTAB) as components of a predicted type I secretion and processing system (RaxA and RaxB). These observations suggest a model where RaxST sulfates a molecule that contains a leader peptide, which is cleaved by the peptidase domain of the RaxB protein and secreted outside the bacterial cell by the RaxABC T1SS.